2023
DOI: 10.3233/jad-220935
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Properties of Eudesmin on a Cellular Model of Amyloid-β Peptide Toxicity

Abstract: Background: Alzheimer’s disease (AD) is a neurodegenerative disorder characterized by progressive cognitive impairment and memory loss. One of the hallmarks in AD is amyloid-β peptide (Aβ) accumulation, where the soluble oligomers of Aβ (AβOs) are the most toxic species, deteriorating the synaptic function, membrane integrity, and neuronal structures, which ultimately lead to apoptosis. Currently, there are no drugs to arrest AD progression, and current scientific efforts are focused on searching for novel lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Recently, Mentese and colleagues reported that vanillic acid exhibited ovoprotective effects in a cisplatin-induced rat model of ovotoxicity by activating Nrf2 [ 37 ]. Furthermore, studies have shown that the renal protective effects of magnolin in rat kidney injury models are attributed to its antioxidative, anti-inflammatory, and antiapoptotic properties [ 51 , 52 ], while eudesmin (a tetrahydrofurofuranoid lignan) has been found to possess neuroprotective properties in an amyloid-β-induced model of Alzheimer’s disease [ 53 ]. These findings lead us to speculate that the ovoprotective effects of MFE may be attributed to the cytoprotective activities of vanillic acid, magnolin, and eudesmin.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Mentese and colleagues reported that vanillic acid exhibited ovoprotective effects in a cisplatin-induced rat model of ovotoxicity by activating Nrf2 [ 37 ]. Furthermore, studies have shown that the renal protective effects of magnolin in rat kidney injury models are attributed to its antioxidative, anti-inflammatory, and antiapoptotic properties [ 51 , 52 ], while eudesmin (a tetrahydrofurofuranoid lignan) has been found to possess neuroprotective properties in an amyloid-β-induced model of Alzheimer’s disease [ 53 ]. These findings lead us to speculate that the ovoprotective effects of MFE may be attributed to the cytoprotective activities of vanillic acid, magnolin, and eudesmin.…”
Section: Discussionmentioning
confidence: 99%
“…At present, the journal boasts an impressive impact factor of 4. Distinguished by its thematic focus on AD pathogenesis and therapeutic interventions, the Journal of Alzheimer’s Disease has recently witnessed noteworthy investigations delving into the ramifications of compounds such as resveratrol, kaempferol, and Eduesmin on AD pathophysiology ( 29 32 ). In essence, the number of articles published by research collectives serves as a testament to their active engagement and contributions within a given scientific sphere.…”
Section: Discussionmentioning
confidence: 99%
“…Evidently, the United States' robust healthcare investments surpassing those of other nations potentially elucidate the concentration of AD and cerebral white matter research publications in this region (27,28). Moreover, it is notable that most collaborative efforts concerning AD and cerebral white matter are anchored in the United States, seamlessly (29)(30)(31)(32). In essence, the number of articles published by research collectives serves as a testament to their active engagement and contributions within a given scientific sphere.…”
Section: Discussionmentioning
confidence: 99%
“…In an article by Daly et al [15], they give insight into understanding the association with intervention; the Alzheimer's Disease-Associated Processes and Targets (ADAPT) ontology provides a new dimension to understanding novel neurodegenerative pathways. Furthermore, Castillo and colleagues [16] highlight the neuroprotective properties of eudesmin, a natural lignin from the tree Araucaria Araucana. This lignan prevents amyloid-␤ peptide toxicity in cell models and may lead to novel molecules in therapeutic intervention.…”
mentioning
confidence: 99%